Uji Antioksidan Batang Waltheria Indica pada Kondisi Minimal di Daerah Gambut - Yuliana Yuliana; Samsul Hadi; Indryani Syarifuddin; Kartini Kartini; Pertiwi Awilda; Sheila Nurrahmah; Siti Rahimah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Free radicals are unpaired electron molecules that are unstable and can attack important macromolecules causing cell damage in the body. Antioxidants themselves are compounds that can prevent oxidative reactions by free radicals. One of the plants that has the potential as an antioxidant is Walther indica. This study aims to determine the antioxidant activity and determine the total flavonoid content of Waltheria indica stem extract. The method used in this study is the DPPH method which is used to determine antioxidant activity. The antioxidant activity of the Waltheria indica ethanol extract was obtained with an IC50 value of 148.7116 ± 2.061 with a moderate antioxidant category.